CURRENT STATE AND PROSPECTS OF ECOLOGICAL TOURISM IN THE CARPATHIAN REGION OF UKRAINE - MOSKVYAK, YAROSLAVA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the main directions of ecotricism development, determines the formation of ecological tourism activities in Ukraine. The main potential of each country or territory is its wealth of ecotourism resources, the most important components are quality and volume, in order to use and develop resources, you need not only to have an idea about them, but also to know a lot.Obviously, the more favorable the climate, fauna or flora or diversity of cultural heritage, the richer the country and the growing demand for this area. Favorable conditions for the development of ecological tourism are the presence of diverse terrain, flora and fauna, as well as access to the sea or ocean, many rivers, lakes, waterfalls and others.Today, global environmental problems are of concern to all mankind. The environmental crisis is a major factor in understanding environmental issues and taking action to improve the situation. Firstly, ecological tourism provides an opportunity for a holistic vision of nature, man and cultural heritage, and secondly, this industry is the most relevant in the Carpathian region.Ecological tourism promotes the development of human culture and helps to acquire new knowledge, thanks to which a person self-improves realizes and improves their recreational and spiritual needs. Ecotourism covers a large sector of the industry from one-day vacations in the city and small excursions for schoolchildren to multi-day treks.By type of classes there are 3 types of ecotourism:• Scientific ecological tourism. Expeditions of scientists, practice of students in reserves, field research (for example, reports on the number of animals) with the involvement of volunteers.• Cognitive ecotourism. Observations of mammals, birds, rare plants, butterflies. Tours to paleontological monuments, ethnographic trips, photo hunting.• Recreational tourism. Active recreation: horseback riding, hiking, biking, mountaineering, rafting, river rafting. Passive recreation: picnics, stays at bases and in tent camps with exploration of the surroundings. [5]Eco-tourism is a type of tourism that involves a cognitive journey to fragile, untouched and relatively untouched natural areas and interesting objects in order to get pleasant emotions from being in a green area and deepen knowledge about it and its inhabitants. Based on the above, we can conclude that eco-tourism is a very important area of tourism today.It is the basic principles of green tourism that help to achieve the set goals for the preservation of ecology and culture of certain regions of the Carpathian region and the world as a whole, where ecological tourism is developing so rapidly.
Keywords: ecological tourism; Carpathian region; ecological route; ecological trail; ecotourism; tourism